Sunnah of Qailulah After Studying: A Study of Living Hadith at Ar-Rasyid Islamic School - Husni, Khoirurrijal; Munandar (Medina-te : Jurnal Studi Islam, 2025)
This study aims to determine the implementation of sunnah qailulah (napping) after learning activities at Pondok Pesantren Modern Ar-Rasyid Pinang Awan, as well as analysing its relevance to the hadith of the Prophet Muhammad SAW, the benefits felt by the students, and the obstacles in its implementation. This research uses a descriptive qualitative approach using field research methods and literature review. Data collection was conducted through in-depth interviews with students, teachers, and ustadzah, as well as direct observation of students' daily activities. Data analysis techniques include data reduction, data presentation, and conclusion drawing using the interactive analysis model by Miles and Huberman. The results showed that sunnah qailulah has become a mandatory routine activity in the pesantren environment as a form of practicing hadith values in the lives of students. Most of the santri consistently perform qailulah (70-90%) and experience significant benefits such as increased learning concentration, physical recovery after morning activities, ease in getting up at night for tahajud, and increased learning effectiveness during the day. The qualitative data collected also showed that qailulah has a positive impact on students' health and productivity. However, obstacles such as lack of awareness among some students and weak supervision were still found. Solutions implemented include educational sanctions and strengthened supervision by caregivers and heads of dormitories. This study shows that sunnah qailulah, if implemented with discipline, can contribute to the spiritual, academic, and health of santri.